Qualidade da informação contábil: Análise dos demonstrativos dos municípios de Minas Gerais - Comissário, Aline Bernardes (2023)
This research aimed to analyze the quality of information in the accounting statements of municipal governments in Minas Gerais through the creation of the Accounting Information Quality Index (IQIC), based on the Accounting Manual Applied to the Public Sector (MCASP), in the Accounting Procedures Asset Management (PCP) established by Ordinance 548/2015 and the Brazilian Accounting Standards Applied to the Public Sector (NBCASP). Firstly, the study outlines the theoretical support of Institutional Theory. Then, it brought the main events that culminated in the convergence to International Public Accounting Standards and the changes brought about by Brazilian Accounting Standards Applied to the Public Sector. By presenting an overview of the Brazilian process, the study develops a timeline with the main regulations on the topic, and ratifies the findings of previous studies. Then, relevant previous studies on the topic of accounting information quality were presented. To find the level of quality of accounting information in the municipalities of Minas Gerais, the Accounting Information Quality Index (IQIC) was created and documentary research was carried out with an exploratory and descriptive nature with the 853 municipalities of Minas Gerais, with data extracted from Siconfi. Finally, it was the analysis of the data where it was possible to quantify the most frequent inconsistencies, the practices not yet adopted and concluded how the quality of the information provided to the National Treasury Secretariat (STN) and the population in general is progressing.